Hormigones livianos - Valdez Guzmán, Luis Fernando (2010)
The present work is about lightweight concretes, and it shows the kindness of this type of concretes, the different kinds of materials that compose it, its properties and characteristics that differ it from the conventional concretes for example its thermal and acoustic insulation, fire resistance and its lightweight. Its lightweight mostly depends on the kind of aggregate; its volumetric density is usually around 300kg/m3 to 1900 kg/m3, which represent a reduction in comparison with normal density concretes. This work shows the classification of this type of concrete, its use, and application in construction. Also presents a brief historical review of the first uses of lightweight concretes, and shows diverse works that have been successfully constructed by lightweight concrete in the last years.